Methodology for Measurement of in vivo Tibiotalar Kinematics After Total Ankle Replacement Using Dual Fluoroscopy - Blair, Dylan J.; Barg, Alexej; Foreman, K. Bo; Anderson, Andrew E.; Lenz, Amy L. (Frontiers in Bioengineering and Biotechnology, 2020)
Biomechanical data could improve our clinical understanding of failures in total ankle replacement (TAR) patients, leading to better surgical approaches and implant designs. Kinematics of the prosthetic tibiotalar joint in TAR patients have yet to be measured using dual fluoroscopy. With dual fluoroscopy, computed tomography (CT) images are acquired to track bone motion. One challenge with this approach is dealing with metal artifact in the CT images that distorts implant visualization and the surrounding bone to implant interfaces. The aim of this study was to develop a methodology to measure in vivo TAR kinematics using inputs of computer-aided design (CAD) models, dual fluoroscopy and CT imaging with metal artifact reduction. To develop this methodology, we created a hybrid three-dimensional (3D) model that contained both: (1) the segmented bone; and (2) the CAD models of the TAR components. We evaluated a patient following total ankle replacement to demonstrate feasibility. The patient performed a self-selected overground walk during which dual fluoroscopy images were collected at 200 Hz. In vivo tracking verifications were performed during overground walking using a distance calculation between the implant articular surfaces to evaluate the model-based tracking 3D solution. Tracking verification indicated realistic alignment of the hybrid models with an evenly distributed distance map pattern during the trial. Articular surface distance calculations were reported as an average of 1.3 mm gap during the entirety of overground walking. The successful implementation of our new tracking methodology with a hybrid model presents a new approach to evaluate in vivo TAR kinematics. Measurements of in vivo kinematics could improve our clinical understanding of failures in TAR patients, leading to better long-term surgical outcomes.